Preparation, Characterization And Properties Of Waste Ferrite Filled Rubber Composites [TN693.I7 S187 2007 f rb]. - Sam, Sung Ting (2007)

(untitled)
Ferrite is a type of magnetic material that is widely used in electrical and electronic industry. This type of material is normally available in ceramic form which is hard and brittle. During grinding process, some waste ferrite would be produced. This type of waste cannot be reused and re-sintered.